ADMISSION TO GRADUATE BUSINESS SCHOOL. - Sapienza, Samuel R. (The Accounting Review, 1959)
In making the decision to enter graduate training for business there are certain factors that you should consider. These are 1. The philosophy of education of the particular schools and your possible reaction to its training techniques. 2. The need for planning; a. To present the best transcript your talents will allow. b. To take the aptitude examination in your junior year, or certainly midway through your senior year. c. To secure letters of recommendation that will give an accurate portrayal of you. d. To visit the school of your choice so that first hand knowledge of the school is yours, as well as other things such as housing, scholarship and loans, and physical facilities. This sort of preparation will assure your application timely and considered attention and enhance the possibilities of admission.